2009
DOI: 10.1161/circep.108.790212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Gap Junction Conduction–Enhancing Antiarrhythmic Peptide GAP-134 Administration on Experimental Atrial Fibrillation in Dogs

Abstract: Background— Abnormal intercellular communication caused by connexin dysfunction may contribute to atrial fibrillation (AF). The present study assessed the effect of the gap junction conduction–enhancing antiarrhythmic peptide GAP-134 on AF inducibility and maintenance in a dog model of atrial cardiomyopathy. Methods and Results— Twenty-four dogs subject to simultaneous atrioventricular pacing (220 bpm for 14 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…These results were comparable with the results obtained after IV administration of ZP123 in a dog model of mitral regurgitation. GAP-134 enhanced gap junctional communication probably by an indirect route, as there was no change in Cx43 and Cx40 mRNA levels, nor in the spatial distribution of Cx43 in the atria after 14 days of oral GAP-134 administration (Laurent et al, 2009). Interestingly, GAP-134 had no effect on the electrophysiological properties of the healthy tissue.…”
Section: Second Generation Antiarrhythmic Peptidesmentioning
confidence: 89%
See 1 more Smart Citation
“…These results were comparable with the results obtained after IV administration of ZP123 in a dog model of mitral regurgitation. GAP-134 enhanced gap junctional communication probably by an indirect route, as there was no change in Cx43 and Cx40 mRNA levels, nor in the spatial distribution of Cx43 in the atria after 14 days of oral GAP-134 administration (Laurent et al, 2009). Interestingly, GAP-134 had no effect on the electrophysiological properties of the healthy tissue.…”
Section: Second Generation Antiarrhythmic Peptidesmentioning
confidence: 89%
“…Hereby, GAP-134 had a robust cardioprotective effect that limited infarct size . The effect of oral administration of GAP-134 (steady-state plasma concentration >100 nM) on conduction abnormalities and atrial fibrillation vulnerability was studied by Laurent et al (2009) in a model of pacinginduced atrial myopathy (Laurent et al, 2009). Simultanous pacing of the right atrium and ventricle induced severe left atrial dilation and increased atrial fibrillation vulnerability.…”
Section: Second Generation Antiarrhythmic Peptidesmentioning
confidence: 99%
“…In a subset of dogs (n ϭ 3), AERP was measured, before and after GAP-134 administration, at cycle lengths of 300 and 200 ms. GAP-134 did not significantly alter the AERP at either cycle length (300 ms, 106.7 Ϯ 4.4 versus 105.0 Ϯ 6.3 ms; 200 ms, 109.2 Ϯ 4.2 versus 113.3 Ϯ 1.7 ms). Although the small sample size used to measure AERP in this study is a limitation, a recent study by Dr. Paul Dorian thoroughly explored the effect of GAP-134 on AERP, and other electrophysiological parameters, in a canine heart failure model of atrial fibrillation (Laurent et al, 2009). In this study, a very small reduction in AERP was observed with GAP-134 at only one cycle length in combination with a large increase in conduction velocity.…”
Section: Gap-134 Limits Af In the Canine Sterile Pericarditis Model 1129mentioning
confidence: 96%
“…Eventually, several of these drugs may not necessarily work, at least under the same concentration and exposure conditions, in all cell types. It is also intriguing that, so far, few connexin channel "openers" have been clearly identified (117,119,124,206,292,432), which delays the development of future strategies aimed at developing a connexin-targeted therapy of several diseases, specifically in humans.…”
Section: G the Pharmacologymentioning
confidence: 99%